A GUIDELINE FOR DEVELOPING THE POTENTIAL OF POLICE TRAINEE BASE ON THE TRISIKKHA PRINCIPLE OF THE PROVINCIAL POLICE TRAINING CENTER REGION 4 - Duanghassadee , Kanit; Thitapanyo, PhramahaMit (Journal of Graduate MCU KhonKaen Campus, 2021)
The objectives of this qualitative research were: 1) to study the principles of the Trisikkha (Threefold Learning) in Theravada Buddhist scriptures; 2) to study the potential status of the police trainees of the Provincial Police Training Center Region 4; 3) to propose a guideline for the development of the potential of police trainees according to the Trisikkha principle of the Provincial Police Training Center Region 4. The research results were as follows: Trisikkha in Theravada Buddhist scriptures: The Trisikkha is a teaching about human development towards the goal of life at two levels, 1) worldly level, to achieve benefits such as healthiness and self-reliance, etc. 2) supramundane level, the ultimate goal as to have wisdom to know the nature of the world and life which makes the mind free. The potential condition of the police trainees of the Provincial Police Training Center Region 4: The Provincial Police Training Center Region 4 organized a study and training course for the police trainees with a process of education, training, basic knowledge of physical, mental, intellectual and social aspects to become a police officer with knowledge, abilities and morality. The guideline for developing the potential of police trainees according to the Trisikkha principle of the Provincial Police Training Center Region 4: (1) Precepts: commanders, trainers and teachers have knowledge and understanding about the precepts and bring the precepts to develop themselves to become a good policeman to train the police trainees to be a good policeman with both physical and verbal honesty and good health; 2) Concentration: supervisors, trainers and teachers have knowledge and understanding of meditation and bring meditation to develop themselves and to organize the training of the mind and emotions for the police trainees to be happy; 3) Intellectual aspect: commanders, trainers and teachers have knowledge and understanding of wisdom and bring intelligence to develop themselves and to provide education and training for the police trainees to be a good police officer with knowledge and understanding how to use wisdom to solve problems, and know how to perform duties and life.